Integrating sustainability values through a workshop on utilizing environmentally friendly materials at SDN 6 Padangsambian Klod as a waste management solution - Fidyariska, Priskylia Jenia; Putra P, Komang Widhya Sedana; Lasmi, Ni Wayan (Nur Science Institute, 2025)
This community service program aimed to increase student's knowledge about environmentally friendly practices and sustainability in the SDN 6 Padangsambian Klod schoolyard. Therefore, major issues were the limited awareness and understanding of environmentally friendly product use and sustainable practices. In handling this, the program employed a participatory and educative approach, hence the combination of workshops with discussions and practical activities such as waste sorting and handicrafts made from recycled materials. It was designed to develop theoretically founded knowledge of ecologically competent practices and their practical implementation in the student's everyday life. Preliminary results reveal that there has been a greater awareness among the students, with 85% showing better understanding and 90% actively engaged in waste sorting and recycling. Another interesting aspect was the commitment expected from the children towards environmental protection, with written pledges made on the